Research Hotspots and Effectiveness of Transcranial Magnetic Stimulation in Pain: A Bibliometric Analysis - Li, Chong; Sun, Mingyu; Tian, Shiliu (Frontiers in Human Neuroscience, 2022)
Transcranial magnetic stimulation, as a relatively new type of treatment, is a safe and non-invasive method for pain therapy. Here, we used CiteSpace software to visually analyze 440 studies concerning transcranial magnetic stimulation in pain research from 2010 to 2021, indexed by Web of Science, to clarify the research hotspots in different periods and characterize the process of discovery in this field. The USA ranked first in this field. Lefaucheur JP, Fregni F, and Andrade ACD made great contributions to this field of study. The most prolific institution was University of Sao Paulo. The four main hot keywords were neuropathic pain, motor cortex, connectivity, and noninvasive brain stimulation. There were three main points that were generally accepted: (1) definite analgesic effect of high-frequency rTMS of M1 contralateral to pain side in neuropathic pain; (2) there are inconclusive recommendations regarding rTMS of the dorsolateral prefrontal cortex (DLPFC) in fibromyalgia and neuropathic pain; (3) there is low-quality evidence that single doses of high-frequency rTMS of the motor cortex may have short-term effects on chronic pain. This bibliometric analysis indicated that prospective, multi-center, large-sample, randomized controlled trials are still needed to further verify the effectiveness of various transcranial magnetic stimulation parameters in pain research.